2020
DOI: 10.1007/s00277-020-03953-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of RNA sequencing and array CGH in the diagnostic workflow of the AIEOP-BFM ALL 2017 trial on acute lymphoblastic leukemia

Abstract: Risk-adapted therapy has significantly contributed to improved survival rates in pediatric acute lymphoblastic leukemia (ALL) and reliable detection of chromosomal aberrations is mandatory for risk group stratification. This study evaluated the applicability of panel-based RNA sequencing and array CGH within the diagnostic workflow of the German study group of the international AIEOP-BFM ALL 2017 trial. In a consecutive cohort of 117 children with B cell precursor (BCP) ALL, array analysis identified twelve ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
4
30
0
Order By: Relevance
“…Multiple entity-defining fusion transcripts are known in BCP-ALLs ( BCR-ABL1 , KMT2A-AFF1 , TCF3-PBX1 , ETV6-RUNX1 ), and a reliable detection is mandatory for every diagnostic workflow. The applied fusion calling procedure identified 97% of the fusions, as detected by gold standard techniques, which is in line with previous RNA-Seq studies in pediatric ALL cohorts that reported detection rates between 91 and 97% [ 3 , 39 41 ]. The number of true positive calls can be increased by considering the overlap of different callers [ 42 ], while simultaneously reducing the number of false negative ones.…”
Section: Discussionsupporting
confidence: 85%
“…Multiple entity-defining fusion transcripts are known in BCP-ALLs ( BCR-ABL1 , KMT2A-AFF1 , TCF3-PBX1 , ETV6-RUNX1 ), and a reliable detection is mandatory for every diagnostic workflow. The applied fusion calling procedure identified 97% of the fusions, as detected by gold standard techniques, which is in line with previous RNA-Seq studies in pediatric ALL cohorts that reported detection rates between 91 and 97% [ 3 , 39 41 ]. The number of true positive calls can be increased by considering the overlap of different callers [ 42 ], while simultaneously reducing the number of false negative ones.…”
Section: Discussionsupporting
confidence: 85%
“…Specific fusion genes have yet to be clarified in at least one-third of B-ALL patients [5,7,8], and our study and the literature verified that early treatment response was the main prognostic factor in these patients [4,5,6,17,21,22,23,24]. In recent studies, NGS has been used to discover more genetic abnormalities in B-ALL, and advanced studies are exploring the relationships among these genetic abnormalities, pathogenesis and outcomes [25,27,28,29]. In this study, NGS detected abnormalities in 62.5% of BM relapsed patients, rare or unreported fusion genes and/or gene mutations were detectable, and adverse molecular genetic abnormalities such as TP53, CREBBP and IKZF1 [30,31] were detected in BM relapsed patients.…”
Section: Discussionsupporting
confidence: 63%
“…Targeted RNA fusion-related gene panel sequencing could be more efficient in clinical applications. Reliable gene fusions could be detected with higher performance price ratio [17,18]. The RNA fusion gene panel used in this study, covered 225 genes, could detect over 900 fusion isoforms, and reached a high validation rate.…”
Section: Discussionmentioning
confidence: 95%